INVADING OTHERS' SPACES: HOW ROMANIAN PUBLIC MUSEUMS REINVENTED THEMSELVES THROUGH IMPROVISATION DURING THE COVID-19 PANDEMIC (Analele Universității București. Limba și literatură română, 2024)
In public museums, there is a plethora of factors that influence the meaningmaking process. In times of great uncertainty, such as the COVID-19 pandemic or the additional blockers brought about by the energy crisis, cultural institutions could not remain unruffled. This research seeks to understand how some museums from Brașov and Bucharest, Romania, adapted to the closure of their physical spaces, a structural crisis that set them against their implicit social role. This article focuses on decoding the discourses that became salient throughout museum workers and on the analysis of the dynamic between the online and offline spheres. Considering all these structural and functional adjustments, this approach will integrate data collected from curators, ethnographers, researchers, and museum managers into previous valuable research on the COVID-19 context.